PENGARUH PERASAN LABU SIAM DALAM MENURUNKAN TEKANAN DARAH: SYSTEMATIC REVIEW - Sukurni Sukurni (NHM PRESS, 2022)
The incidence of hypertension from year to year continues to increase. Apart from being asymptomatic, it also causes various complications to death. Handling hypertension can be done pharmacologically and non-pharmacologically. Chayote is one of the non-pharmacological treatments and is a type of vegetable that is commonly consumed by the community. But people do not know the use of chayote as herbal therapy for hypertension. The purpose of this study was to determine the effect of giving chayote on blood pressure in patients with hypertension. This research was limited from 2000 to 2021 and found 6 eligible articles sourced from the Google Scholar search engine with the keywords “chayote, secium edule, blood pressure, hypertension. The results of the study reported that from 6 articles it was found that chayote juice was effective in reducing blood pressure in hypertensive patients with a dose of 100-250gr per day for 7-11 days